Self-assembled nanomaterials for biosensing and therapeutics: recent advances and challenges. Issue 9 (1st April 2021) - Huang, Shan; Song, Yuexin; He, Zhimei; Zhang, Jian-Rong; Zhu, Jun-Jie
Abstract : Self-assembled nanomaterials (SANs) exhibit designable biofunctions owing to their tunable nanostructures and modifiable surfaces. Abstract : Self-assembled nanomaterials (SANs) exhibit designable biofunctions owing to their tunable nanostructures and modifiable surface. Various constituent units and multi-dimensional structures of SANs provide unlimited possibilities for numerous applications. This review emphasizes the recent development of SANs in the fields of biosensing, bioimaging, and nano-drug engineering. The unit type, design concepts, material advantages, assembly driving force, nanostructure effects, drug loading performance, etc . are discussed and summarized. Finally, we briefly summarize how to assemble unique nanomaterials and point out the key challenges in this field.